Programmed photosensitizer conjugated supramolecular nanocarriers with dual targeting ability for enhanced photodynamic therapy. Issue 80 (16th September 2016) - Tong, Hongxin; Du, Jianwei; Li, Huan; Jin, Qiao; Wang, Youxiang; Ji, Jian
Abstract : A programmed multistage targeted supramolecular nanocarrier was developed for enhanced photodynamic therapy. Abstract : A programmed supramolecular nanocarrier was developed for multistage targeted photodynamic therapy. This smart nanocarrier exhibited enhanced cellular uptake and controlled mitochondria targeting, as well as an excellent photodynamic therapeutic effect after light irradiation.